Laudato Si' - a call for all people to dialogue about our common home - Glancy, Christopher (Medellín. Biblia, Teología y Pastoral para América Latina y El Caribe, 2016)
In his encyclical Laudato Si, Pope Francis invites all of humanity into a dialogue about the care of our common home. This article explores how Francis uses the local magisterium of Bishops’ Conferences from around the world, the historical magisterium of the teaching of earlier popes, and also the teaching of an Ecumenical Patriarch, along with his own creative thinking to present a cohesive teaching of the Church on the care of creation and of the poor. The encyclical presents: aspects of the current crisis; principles from the Judeo-Christian tradition on environment; roots and causes of the contemporary situation; proposals for dialogue and action; and guidelines for human development based on Christian spiritual experience. This article focuses on the common good in the creation tradition, a significant root cause in consumerism, and a way forward with Francis of Assisi through contemplation, conversion and creativity.